Deságios nos leil\~oes de linhas de transmiss\~ao de energia elétrica no Brasil (2011-2023) - Flávio Augusto A. A. H. Martins (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– This research aimed to understand how the profile of bidders in transmission auctions evolved between 2011 and 2023, and which factors explain the probability of winning and the discounts observed in each bidder's offer. The results of the econometric estimations indicate a paradigm shift, as variables related to the origin of social capital, economic sector, capacity constraints, and interdependence did not reveal sample selection bias between winning and losing firms. At the firm level, the estimations showed that companies in the electricity sector had a higher probability of winning and offered larger discounts, while investment capacity constraints were statistically significant for a lower chance of winning - consistent with expectations, given that many projects require substantial investments.
Keywords: O18; L94; K23; 330; transmission lines; electric power industry; auctions